'We need to talk about Bona': An autoethnographic account of fostering an unaccompanied asylum seeker. Issue 1 (21st April 2021) - Daly, Maura; Smith, Mark
Abstract : This article offers an account of the authors' experiences as foster carers for an unaccompanied asylum seeker (and through him, supporting other asylum-seeking boys). We are both qualified and experienced social workers, now social work academics living and working in Scotland, whose practice is informed by socio-pedagogical perspectives. Our backgrounds have given us unique and finely grained insights into the daily care issues facing young asylum seekers set against a backdrop of global movement. We discuss the need to provide care that offers cultural safety; the centrality within this of recognising and seeking to understand religious beliefs and practices; the experiences of young people growing up in conditions of liminality, negotiating two very different cultures; the inadequacy of current social work responses; the importance of everyday care and relationships and the need for a curious and reflexive orientation from caregivers.